Assessment of safety management system on energy investment risk using house of quality based on hybrid stochastic interval-valued intuitionistic fuzzy decision-making approach. (September 2021) - Fang, Su; Zhou, Pengfei; Dinçer, Hasan; Yüksel, Serhat
Highlights: Safety management system is evaluated for the energy investment risks. IVIF DEMATEL, IVIF TOPSIS and IVIF VIKOR are considered. Global economic uncertainty is the most important criterion. Competitive environment is the most crucial item of safety management. The market must be effectively monitored for this purpose. Abstract: The purpose of the study is to construct a novel hybrid stochastic interval-valued intuitionistic fuzzy (IVIF) decision approach to the house of quality (HoQ)-based analysis of safety management system with the respect to the energy investment risks. For this purpose, two step analyses of IVIF decision making models by using the Decision-Making Trial and Evaluation Laboratory (DEMATEL) and Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) are applied for weighting and ranking criteria of energy investment risks and safety management system, respectively. Additionally, Vise Kriterijumska Optimizacija I Kompromisno Resenje (VIKOR) methodology is also taken into consideration to make a comparative evaluation. The novelty of study is to propose a new hybrid decision making model based on IVIF sets and to analyse the probability and non-probability degrees of the extreme values with the stochastic data comparatively for the robustness check. The results show that global economic uncertainty is the most important criterion while the changes in the policy and regulatory at the country level has relatively the weakest importance among the energy investment risk. Additionally, the competitive environment is defined as the most prominent factor of safety management system on the energy investment risk when the HoQ-based fuzzy matrix is applied. However, the analysis demonstrates that hybrid decision making approaches based on interval-valued fuzzy sets and stochastic values provide the coherent results for weighting the criteria of energy investment risks and ranking the factors of the safety management system with HoQ. Based on these results, it is understood that uncertainties in the global economy increase investors' future worries. When global economic uncertainties are high, the market must be effectively monitored, and the necessary actions should be taken immediately. For this purpose, the necessary training should be given to the personnel currently working in these companies. In this framework, staff-based training programs should be prepared according to the job descriptions of the employees. Additionally, regarding the new recruitment personnel process, qualified employees should be selected based on the job descriptions.